Advanced Computer Techniques in Applied Electromagnetics - Wiak, Sławomir (IOS Press, 2013)
This book contains papers presented at the International Symposium on Electromagnetic Fields in Electrical Engineering ISEF’07 which was held in Prague, the Czech Republic, on September 13–15, 2007. ISEF conferences have been organized since 1985 as a common initiative of Polish and European researchers who deal with electromagnetic field applied to electrical engineering. Until the present the conferences have been held every two years either in Poland or in one of European academic centres renowned for electromagnetic research. Technical University of Prague and the Chech Academy of Sciences make Prague be such a centre. Additionally, Prague is well-known in the world for its beauty and charm and it is called “Golden Prague”. The city of Prague is one of the six most frequently visited cities in Europe. Indeed, it is indisputable that Prague can attract every has the opportunity to visit it.